Gimkit: An Effective Digital Learning Media for Teaching Vocabulary at an Islamic Junior High School - Imaniar Nur Syahadah; Mukminatus Zuhriyah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Vocabulary mastery is a fundamental component of English language proficiency, yet instruction in many Indonesian EFL classrooms often lacks engagement due to a heavy reliance on traditional rote memorization. This study aims to examine the effectiveness of Gimkit, a digital game-based learning platform, in improving students’ vocabulary mastery specifically within an Islamic junior high school context. Employing a quantitative pre-experimental one-group pre-test and post-test design, the research involved 32 seventh grade students at an Islamic Junior High School in Jombang. The research instrument was a 20-item multiple-choice vocabulary test focused on the topic “Telling Time, “Which was administered before and after the two-session treatment. Data were analyzed using a Paired Sample t-Test through SPSS version 27 to determine statistical significance and Cohen’s d to measure effect size. The results revealed a significant improvement in students’ vocabulary mastery, with the mean score increasing from 73.28 in the pre-test to 86.25 in the post-test. Statistical analysis showed a Sig. (2-tailed)value of 0.000 (p < 0.05) and a large effect size of 1.379. These findings indicate that Gimkit is an effective digital learning medium for enhancing vocabulary mastery by promoting active engagement, competitive gameplay, and instant feedback. Consequently, English teachers are encouraged to integrate such game-based platforms to create more interactive and student-centered learning environments.